Systematic Review of Data-Integrated GTM Strategies for Logistics and Postal Services Modernization - Abiodun Yusuf Onifade,; Remilekun Enitan Dosumu,; Abraham Ayodeji Abayomi,; Oluwademilade Aderemi Agboola,; Jeffrey Chidera Ogeawuchi, (International Journal of Scientific Research in Science and Technology, 2024)
The logistics and postal services sectors are undergoing rapid transformation driven by the pressures of digitization, evolving customer expectations, and global competition. At the core of this evolution is the strategic integration of data into Go-To-Market (GTM) strategies to modernize operations, enhance service delivery, and increase market agility. This systematic review aims to critically examine and synthesize existing literature on data-integrated GTM strategies in the context of logistics and postal services modernization. Following PRISMA guidelines, peer-reviewed journal articles, industry reports, and case studies from 2010 to 2024 were collected from leading databases including Scopus, Web of Science, and IEEE Xplore. The review identifies key themes in the deployment of data-driven GTM approaches, including predictive analytics for demand forecasting, real-time operational monitoring, customer segmentation, and digital platform integration. Findings reveal a significant shift from traditional GTM methods to agile, data-centric models that emphasize customer experience, service efficiency, and cross-functional alignment. Data integration has been instrumental in enabling predictive planning, last-mile optimization, and personalized marketing, with technologies such as IoT, AI, and big data analytics playing pivotal roles. However, challenges persist, including data silos, poor interoperability, regulatory compliance, and workforce skill gaps. Notably, the review highlights the disparity in adoption levels across regions and between private and public service providers, emphasizing the need for tailored strategies. The review contributes a comprehensive framework for understanding how data-integrated GTM strategies drive modernization outcomes in logistics and postal services. It underscores the importance of aligning data capabilities with organizational goals and customer expectations. The review concludes by recommending further empirical research on implementation models, return on investment (ROI) metrics, and policy implications to support sustainable digital transformation in these sectors. This work provides valuable insights for practitioners, policymakers, and researchers seeking to leverage data as a strategic asset in GTM planning and service innovation.
Keywords: Systematic review; Data-integrated; GTM; Strategies; Logistics; Postal services; Modernization